Disaster response in selected municipalities of Pangasinan - Pulido, Oscar Galang Jr. (Panpacific University : [s.n.], 2018)
This study aimed to determine the disaster response of the three identified adjacent Municipalities in Pangasinan namely Binalonan, San Manual and Laoac. Specifically, it sought to determine the adequacy of emergency supplies and rescue materials, the level of response in the three phases of disaster, the difference in the perception of the LGU Personnel and the residents as to the level of disaster response, the relationship between adequacy of emergency supplies and equipment and disaster response, the degree of seriousness of the problems encountered during disaster response, and the action plan that can be proposed to address the problems encountered during disaster response. Descriptive survey method of research was used. Frequency counts, percentages, weighted average point, Analysis of Variance and Pearson-R Correlation were the statistical tools used in the analysis of data.
Bibliography: pages 110-113.
CHED-La Union
Keywords: Disaster relief